A model for selection of suppliers by comparison of two clustering algorithms. (25th January 2010) - Parthiban, P.; Punniyamoorthy, M.; Ganesh, K.; Janardhana, G. Ranga
This paper deals with the study of consumer durables suppliers and retailers, and assessment of these suppliers with multiple products and multiple brands based on multiple criteria. The objective is to identify the set of suppliers for set of products. We develop two phase logical model. The first phase includes Fast-Slow-Non moving (FSN) and High-Medium-Low (HML). FSN and HML analysis were carried out to categorise the products. The second phase is the cluster analysis. We used two clustering methods, divisive and K-means clustering for comparison. Cluster analysis assists in selecting the final list of suppliers by parameterised clustering.